THE ESSENCE AND FORMS OF THE TECHNOLOGIES OF IMPROVING LEARNING MATERIALS BASED ON IMITATION-VARIATION IN INDEPENDENT EDUCATION - Obidov Jamshidbek Gayratjon o’g’li (Journal of new century innovations, 2023)
Abstract: In this article reveals the scientific significance of simulation technologies in the educational process of higher education. On the basis of the technology of simulation modeling, the problems of the formation and development of the pedagogical activity of the educational process are investigated.